2010
DOI: 10.1210/en.2010-0672
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Role for Insulin-Like Growth Factor Binding Protein (IGFBP)-3 in Metabolic Regulation

Abstract: IGF-binding protein (IGFBP)-3 is a metabolic regulator that has been shown to inhibit insulin-stimulated glucose uptake in murine models. This finding contrasts with epidemiological evidence of decreased serum IGFBP-3 in patients with type 2 diabetes. The purpose of this study was to clarify the role of IGFBP-3 in metabolism. Four-week-old male IGFBP-3(-/-) and control mice were subjected to a high-fat diet (HFD) for 12 wk. IGFBP-3(-/-) mice were heavier before the initiation of HFD and at the end of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
(41 reference statements)
5
30
0
Order By: Relevance
“…In contrast, hIGFBP-3 enhanced adipocyte differentiation and stimulated the lipogenic enzyme glycerol-3-phosphate dehydrogenase in visceral and sc preadipocytes (44). This observation is in line with the increase in serum glycerol in the Tg mice and with a recent report that IGFBP-3-null mice had reduced adipose tissue mass and circulating triglycerides (10). It has also been suggested that ternary complex formation between IGF-1, IGFBP-3, and ALS is important for adipogenesis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, hIGFBP-3 enhanced adipocyte differentiation and stimulated the lipogenic enzyme glycerol-3-phosphate dehydrogenase in visceral and sc preadipocytes (44). This observation is in line with the increase in serum glycerol in the Tg mice and with a recent report that IGFBP-3-null mice had reduced adipose tissue mass and circulating triglycerides (10). It has also been suggested that ternary complex formation between IGF-1, IGFBP-3, and ALS is important for adipogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…However, mice overexpressing hIGFBP-3 [phosphoglycerate kinase (PG-K)BP3] or its Gly56/Gly80/Gly81-mutant (PGKmutBP3) under the PGK promoter are not insulin-resistant (8,9), but they are glucose intolerant and have impaired ␀-cell function (9). Also, a recent report indicates that IGFBP-3-null mice have fasting hyperglycemia with normal insulin sensitivity (10). IGFBP-3 levels increase in mice to peak around age 4 weeks and then decline (11).…”
mentioning
confidence: 99%
“…Moreover, each experiment was done in different conditions, such as diet (fasting, fed with normal chow, or fed high-fat diet), and age at the time of experiment. Nevertheless, it is of note that IGFBP-3 KO mice with a high-fat diet had heavier weight compared with WT and showed fasting hyperglycemia and hyperinsulinemia, indicating insulin resistance, even not in glucose tolerance test18).…”
Section: Igfbp-3-knockout (Ko) Mice Studymentioning
confidence: 94%
“…In contrast, IGFBP-3 KO mice exhibited normal insulin level and glucose response after glucose challenge. More recent study in IGFBP-3 KO mice with a high-fat diet demonstrated that IGFBP-3 KO mice exhibited heavier weight, decreased resting metabolic rate, and elevated fasting glucose and insulin levels18). However, IGFBP-3 KO mice had relatively normal glucose response after glucose challenge, and increased basal hepatic glucose production, but after insulin stimulation during hyperinsulinemic clamps, indicating that IGFBP-3 KO mice preserve insulin sensitivity despite evidence of increased basal glucose turnover.…”
Section: Igfbp-3-knockout (Ko) Mice Studymentioning
confidence: 99%
“…Yamada et al [22] have reported decreased serum IGFBP-3 in patients with type 2 diabetes and studies on patients with type 1 diabetes also found the concentration of IGFBP-3 to be lower [23,24]. According to Cortizo et al, levels of IGF-I and IGFBP-3 were comparable in the type 2 diabetic patients and controls for the population ranging from 35 to 70 years [9].…”
Section: Discussionmentioning
confidence: 96%